Genetic susceptibility to anthracycline‐related congestive heart failure in survivors of haematopoietic cell transplantation. (8th August 2013) - Armenian, Saro H.; Ding, Yan; Mills, George; Sun, Canlan; Venkataraman, Kalyanasundaram; Wong, Florence Lennie; Neuhausen, Susan L.; Senitzer, David; Wang, Shirong; Forman, Stephen J.; Bhatia, Smita
Summary Haematopoietic cell transplantation (HCT) survivors are at increased risk for developing congestive heart failure (CHF), primarily due to pre‐HCT exposure to anthracyclines. We examined the association between the development of CHF after HCT and polymorphisms in 16 candidate genes involved in anthracycline metabolism, iron homeostasis, anti‐oxidant defence, and myocardial remodelling. A nested case‐control study design was used. Cases (post‐HCT CHF) were identified from 2950 patients who underwent HCT between 1988 and 2007 at City of Hope and had survived ≥1 year. This cohort formed the sampling frame for selecting controls (without CHF) matched on: age, race/ethnicity, cumulative anthracycline exposure, stem cell source (allogeneic, autologous), and length of follow‐up. Seventy‐seven cases with pre‐HCT germline DNA and 178 controls were genotyped. Multivariate analysis revealed that the odds of CHF was higher in females [Odds Ratio (OR) = 2·9, P < 0·01], individuals with pre‐HCT chest radiation (OR = 4·7, P = 0·05), hypertension (OR = 2·9, P = 0·01), and with variants of genes coding for the NAD(P)H‐oxidase subunit RAC2 (rs13058338, 7508T→A; OR = 2·8, P < 0·01), HFE (rs1799945, 63C→G; OR = 2·5, P = 0·05) or the doxorubicin efflux transporter ABCC2 (rs8187710, 1515G→A; OR = 4·3, P < 0·01). A combined (clinical and genetic) CHF predictive model performed better [area under the curve (AUC), 0·79] than the genetic (AUC = 0·67) or the clinical (AUC = 0·69) models alone.